Classification of Antonyms in Kokborok - Debbarma, Biman (Nepalese Linguistics, 2024)
This paper emphasizes on the classification of antonyms in Kokborok, dealing with the nuances of linguistic oppositeness. The classification includes of two types; semantic classification and morphological classification. The semantic classification has gradable and non-gradable oppositeness. A subtype of morphological classification is derivational opposite which are formed by the addition of negative suffixes in Kokborok. This study employs qualitative data collection methods, emphasizing different oppositeness used in the language. It then diligently looks upon each antonym types, offering comprehensible examples to demonstrate their distinctive meanings of oppositeness in the language.